AESTHETIC DIMENSIONS OF OLA ROTIMI’S THEATRE - Ejeke, Odiri Solomon (UI Scholars Hub, 2021)
The study examines Ola Rotimi’s Theatre from both the literary and theatrical perspectives. The study contends that Ola Rotimi created/developed simplicity of style both in his playwriting and in theatre practice. The study also notes that Rotimi has created the drama and theatre of lasting quality through his knowledge of the culture and tradition of his people and his copious deployment of Para-linguistic aesthetics in his plays. Rotimi anchores all these on his knowledge of world theatre in his practice, thus creating the phenomenon of total theatre. The study concludes that the laws of the theatre are provisional and subject to change, derived from creativity and not from theory.